2020
DOI: 10.1111/jav.02379
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and female body condition are related to night incubation behavior in wood ducksAix sponsa

Abstract: For many animals, parental care behavior is an important aspect of their life history that affects both parents and offspring. In birds, one of the most important parental care behaviors is incubation, which is costly to the parent but directly influences embryonic development and fitness of offspring. Some birds exhibit the intriguing behavior of partially incubating their eggs prior to clutch completion for only a portion of each day. This partial incubation is characterized by lower incubation temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 100 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…In this scenario, it might be expected that females with better body condition could increase nocturnal nest attentiveness faster and reach nocturnal full incubation earlier, although a previous study found that better body condition correlated with longer partial nocturnal incubation periods in precocial Wood Ducks Aix sponsa (Grimaudo et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it might be expected that females with better body condition could increase nocturnal nest attentiveness faster and reach nocturnal full incubation earlier, although a previous study found that better body condition correlated with longer partial nocturnal incubation periods in precocial Wood Ducks Aix sponsa (Grimaudo et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This egg was secured in the centre of the clutch, but attached to a spring, which kept the egg stationary but flexible. When the temperature data from the stationary logger indicated that the hen had started partial incubation at night and thus, would shortly begin full incubation (Grimaudo et al., 2020), we replaced six eggs in the nest with our mobile temperature loggers, which had no cables or wires and could be freely moved and rotated by the hen. Wood ducks are an ideal species for this type of study because in our study sites they are known to readily accept and incubate eggs from other hens (brood parasitism), as well as free‐moving wooden eggs, even with imperfections and holes (S. F. Hope, R. A. Kennamer, S. E. DuRant, W. A. Hopkins, pers.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, under cold conditions, sanderlings may need more time for energy replenishment, especially to compensate for the low availability of arthropods. However, this effect is likely mediated by the body condition, with individuals in better conditions having more energy to invest in reproduction [ 56 , 57 ] and experience fewer energetic constraints than those in poorer condition. While declining temperatures trigger extended recesses regardless of body condition, the duration of extended recesses only increases for individuals below a given threshold of body condition (see section 3d; figure 3 b ).…”
Section: Discussionmentioning
confidence: 99%